Towards Creative Europe: Irish Performing Arts Organisations and the EU Culture Programme - Carew, Michelle (Irish Journal of Arts Management and Cultural Policy, 2013)
This paper presents statistical and qualitative research on the Irish peforming arts sector’s engagement with the EU Culture Programme from the Irish perspective with an emphasis on the performing arts sector arguing for a clear national policy on the provision of support to organisations in a position to leverage EU cultural funds. Research was conducted to examine engagement with the EU Culture Programme from the Irish perspective with an emphasis on the performing arts sector. The research aimed to quantify actual levels of Irish participation and identify the barriers to, and benefits for, Irish performing arts organisations pursuing project funding from the EU Culture Programme. Extant statistical data was analysed to create a macro picture of overall Irish participation expressed through quantitative findings. These statistical findings were then examined through qualititative research conducted with individuals and organisations representing Irish international performing arts experience on either a practical or policy level. With an ultimate benefit to the artistic practice of the participating organisation, as well as to the Irish performing arts ecology as a whole, the research findings demonstrate the need for a clear national policy on the provision of support to organisations in a position to leverage EU cultural funds.